De vogal para semivogal: hiperalçamento vocálico - Sérgio Linard; Carla Maria Cunha; Thayná Cristina Ananias (Revista Odisséia)
This research aims to establish semivowels as vowel variants in Brazilian Portuguese, based on the process of hyper-raising. The development of this study starts with the observation of the liminal state in which semivocalic segments are found, from the perspectives of normative grammarians and of linguists. The articulatory-functional nature of vowels and semivowels in the formation of diphthongs is also considered. Subsequently, the process of raising in the language applied to the variation between vowel segments is outlined. Since semivowels are not considered in the raising process, the process of vowel hyper-raising is proposed to characterize phonetic forms resulting from variation with the surpassing of articulation in the vowel area. The analysis is based on the Feature Geometry of Clements and Hume (1995) and Structural Phonology, primarily focused on the phonetic-phonological description presented by Mattoso Camara Jr. (1988; 2015) for Brazilian Portuguese. The analysis of the described hyper-raising results in the understanding that the semivowels [j] and [w] vary with rounded anterior and posterior vowels, respectively, paying attention to the loss of the nucleus position of a vowel. Two articulatory interpretations can be applied to this segment: (i) the constitution of a complex segment by adding, in the vowel geometry, [coronal] or [labial] and [dorsal] Consonant Place feature(s); and (ii) the constitution of a consonantal segment whose geometry differs from that of a vowel by the absence of the Opening node. Therefore, the focus of this research establishes hyper-raising as a motivator for the creation of diphthongs in Brazilian Portuguese.